2019
DOI: 10.1155/2019/3637453
|View full text |Cite
|
Sign up to set email alerts
|

Water Extract of Acori Graminei Rhizoma Attenuates Features of Rheumatoid Arthritis in DBA/1 Mice

Abstract: The dry rhizome of Acorus gramineus Solander, known as Acori Graminei Rhizoma, is used to treat dementia, stroke, eczema, and indigestion in traditional Chinese medicine, traditional Korean medicine, and traditional Japanese Kampo medicine. Previous studies have reported that Acori Graminei Rhizoma extract ameliorated cognitive impairment in Aβ1-42 injected mice. However, the effect of Acori Graminei Rhizoma on type II collagen induced arthritis (CIA) has not been elucidated. Thus, we evaluated the water extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To examine the therapeutic effect of LMT-28 in an animal CIA model, vehicle, LMT-28 (50, 5, or 0.5 mg/kg), or MTX (5 mg/kg) were orally administered to CIA mice daily after primary immunization. MTX is a disease-modifying anti-rheumatic drug, [12][13][14] used in conventional therapy for RA. Representative photographs displaying morphological changes in the left front paws of mice from each group on day 75 after treatment are shown in Figure 1A.…”
Section: Lmt-28 Suppresses Symptoms Of Cia Mice and Secretion Of Inflammatory Cytokinementioning
confidence: 99%
“…To examine the therapeutic effect of LMT-28 in an animal CIA model, vehicle, LMT-28 (50, 5, or 0.5 mg/kg), or MTX (5 mg/kg) were orally administered to CIA mice daily after primary immunization. MTX is a disease-modifying anti-rheumatic drug, [12][13][14] used in conventional therapy for RA. Representative photographs displaying morphological changes in the left front paws of mice from each group on day 75 after treatment are shown in Figure 1A.…”
Section: Lmt-28 Suppresses Symptoms Of Cia Mice and Secretion Of Inflammatory Cytokinementioning
confidence: 99%
“…These findings suggest that Ginsenoside Rg1 has neuroprotective effects in AD rats [ 230 ]. Acori graminei Rhizoma (AGR) is a TCM used for AD with fewer side effects, but the underlying mechanism is unclear [ 231 ]. Recently, both in vivo and in vitro experiments have demonstrated that the combination of AGR and ginsenoside Rg1 is able to suppress HO-1 expression by increasing miR-873-5p expression, thereby attenuating miR-873-5p-mediated neuronal cell apoptosis and the cognitive dysfunction in mice with AD [ 232 ].…”
Section: Mechanism Of Saponins In Treating Alzheimer’s Diseasementioning
confidence: 99%